2015
DOI: 10.1038/nsmb.3087
|View full text |Cite
|
Sign up to set email alerts
|

Impact of holdase chaperones Skp and SurA on the folding of β-barrel outer-membrane proteins

Abstract: Chaperones increase the folding yields of soluble proteins by suppressing misfolding and aggregation, but how they modulate the folding of integral membrane proteins is not well understood. Here we use single-molecule force spectroscopy and NMR spectroscopy to observe the periplasmic holdase chaperones SurA and Skp shaping the folding trajectory of the large β-barrel outer-membrane receptor FhuA from Escherichia coli. Either chaperone prevents FhuA from misfolding by stabilizing a dynamic, unfolded state, thus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
126
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 113 publications
(141 citation statements)
references
References 62 publications
15
126
0
Order By: Relevance
“…2). The importance of SurA in OMP biogenesis arises from its dual functions, both of which are incorporated in OMPBioM: (i) SurA can bind to uOMP, thereby preventing aggregation, and (ii) SurA can facilitate the folding of uOMP (13)(14)(15)(16)(17)22). Because SurA plays a prominent role in OMP folding, the loss of SurA in vivo results in the induction of the σ E stress response (11,13), a regulatory mechanism caused by the accumulation of unfolded protein in the periplasm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2). The importance of SurA in OMP biogenesis arises from its dual functions, both of which are incorporated in OMPBioM: (i) SurA can bind to uOMP, thereby preventing aggregation, and (ii) SurA can facilitate the folding of uOMP (13)(14)(15)(16)(17)22). Because SurA plays a prominent role in OMP folding, the loss of SurA in vivo results in the induction of the σ E stress response (11,13), a regulatory mechanism caused by the accumulation of unfolded protein in the periplasm.…”
Section: Resultsmentioning
confidence: 99%
“…Many in vitro and in vivo studies have investigated various components involved in this pathway (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). However, in vitro experiments typically characterize individual components in isolation, and in vivo studies are often incapable of deciphering how specific components are responsible for observed phenomena.…”
mentioning
confidence: 99%
“…proteins populate a dynamic ensemble of conformational states and transit between multiple short-lived interaction sites when bound to chaperones such as Skp, SurA, and Spy during trafficking through the bacterial periplasm (19)(20)(21). Nevertheless, the nature and dynamics of the targeting factors/chaperones in these complexes, and how these properties help guide substrate proteins to the target membrane, have not been addressed.…”
Section: Significancementioning
confidence: 99%
“…The TA-induced opening of Get3 further suggests that the TA substrate explores alternative sites and conformations for interacting with Get3 besides the previously observed docking of the TA-TMD at the well-defined hydrophobic groove in closed Get3, and that, collectively, these alternative Get3-TA interaction modes are energetically more favorable than the established mode. In analogy to membrane protein substrates bound to the Skp and SurA chaperones (19,20), it is plausible that TA substrates sample multiple transient interaction sites during Get3 opening, and TAs could be retained because interaction with alternative sites in Get3 is more favorable than with solvent. This model would explain, in part, the weak electron density for TATMDs in previous Get3•TA structures (13).…”
Section: -H)mentioning
confidence: 99%
“…The inner cavity of Skp may protect the denatured OmpA from DegP, but there is no apparent structure in SurA that may block DegP access (42,43). It was also reported that Skp binds to OMPs more tightly than SurA (44,45). Since SurA is more important for OMP biogenesis (35), the efficient degradation of OmpA by activated DegP may indicate that the lower levels of OMPs in the envelope stress is the result of not only the transcriptional downregulation of OMPs but also the direct DegP proteolysis of OMPs en route to the outer membrane.…”
Section: Discussionmentioning
confidence: 99%